Assessment of organic inputs against pest control in organic rice farming in Nalgonda District, Southern Telangana Zone - Shankar, M; Shankaraiah, M; Bharath, T; Pallavi, S; Khan, M A Aariff; Sumalini, K (Indian Journal of Plant Protection, 2024)
An on-farm paddy trial to assess the performance of organic inputs in organic farming to control pests was carried out on farmers’ fields in the KVK adopted villages, Nalgonda district, Telangana State during Kharif 2020 and 2021. The results over the two years envisaged that mean percent damage of dead hearts (0.3%) and white ear heads (1.7%) caused by yellow stem borer were non significant in organic farming against farmers’ practice (0.8%) and (12.8%), respectively. The percent silver shoot damage due to gall midge and leaf folder damage were low in the demonstrated plots (0.5% and 3.3%) compared to farmers’ practice (0.8% and 8.7%). At 60 and 75 DAT, BPH population was low in demonstrated plots (3.5 and 1.5 no’s/hill) as compared to farmers’ practice (8.5 and 4.5 no’s/hill), respectively. The mean pheromone trap catches recorded in the demonstrated plots were 5.7moths/trap/week. Demonstrated plot recorded significantly low mean grain yield (4925.0 kg/ha) as compared to farmers’ practice (6079.2 kg/ha) and the percent decrease was -19.0%. The demonstrated plots obtained mean higher gross returns of Rs. 1,46,066.7/ha and net returns of Rs. 1,01,525.0/ha than in the farmers’ practice of Rs. 1,16,964.6/ha and Rs. 62,131/ha, respectively. The average highest benefit-cost ratio was observed in demonstrated plots.